Measuring Drug Occupancy in the Absence of a Reference Region: The Lassen Plot Re-Visited - Cunningham, Vincent J; Rabiner, Eugenii A; Slifstein, Mark; Laruelle, Marc; Gunn, Roger N (Journal of cerebral blood flow and metabolism, 2010)
Quantitative estimation of neuroreceptor occupancy by exogenous drugs using positron emission tomography is based on the reduction in the total volume of distribution (VT) of site-specific radioligands after drug administration. An estimate of the distribution volume of free and nonspecifically bound radioligand (VND) is also required to distinguish specific from total binding. However, a true reference region, devoid of specific binding, is often not available. We present a transformation of a graphical method, originally introduced by Lassen, using regional estimates of VT alone to determine occupancy, together with an extension that does not require baseline data.